Caracterisation De La Consommation Des Produits Laitiers Chez Les Etudiants De L’universite Ibn Tofail, Kenitra, Maroc: Etude Descriptive - Najia Ouazzani Taybi; Amine Arfaoui; Milouda Chebabe; Ebrahim Alwashali; Mohammed Ouhssine; Mohamed Fadli (European Scientific Journal, ESJ, 2016)
This work studies the consumption by students of the University Ibn Tofail (Morocco) of a number of dairy products, including milk, yogurt, cheese and butter. The survey sample of the population was random and was composed of 314 students; (58.6% women and 41.4% men). The results of the survey show that 89% of the surveyed population consume dairy products while 11% did not consume them. Of those, 57.3% of the population prefer to consume pasteurized milk and 36% prefer fresh milk, 84% consume yogurt, 84% consume cheese, 55% consume butter and 75% consume milk-based nutraceuticals. The study explored reasons for not consuming more dairy products. 57% of the population surveyed responded that the price of the product is the main reason for not consuming more, 11.8% of this population responded that it is a lack of interest in the product and distrust of the nutritional value of the products, while 19.8% of the population suggested that the lack of availability of these products in the market is the cause.